Art Departments: the importance of research and concept design in pre-production process in a film production / Ammar Fadhli Bahtiar - Bahtiar, Ammar Fadhli (Faculty of Art and Design, 2015)
The purpose of this research is to investigate and analyse how a "thorough" research and concept design can improve the quality of our local film. Concept design can be most easily defmed by breaking the two words down to their individual meanings. In advertising, the term 'concept' is a briefly stated clear idea around which ad or marketing campaign is organized. In a product development, concept is a clear, detailed description of the attributes and benefits of a new product that addresses the needs of the targeted customers. Concept is the reasoning behind an idea, strategy, or proposal with particular emphasis placed on the benefits brought on by that idea. Design is the collection of the ideas that help to serve a purpose. Concept design is common term used in an industrial design, architectural design and engineering but not always being used in our local film in Malaysia except for 3D animation film. Long before a single foot of film rolls, the actors step out of their trailers, or a dab of paint touches the first set~ designers and illustrators - with input from the director - work to define every aspect of the look of the film. It is an organic process, moving from the very general to the very specific through months of collaboration.